2014
DOI: 10.1016/j.medici.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

How useful is antireflux surgery in lung transplant patients with gastroesophageal reflux?

Abstract: NF has been established as a safe operation for lung transplant patients. Late Nissen fundoplication did not improve lung function significantly amongst lung transplanted patients; however, patients with symptomatic GERD may have benefited from Nissen fundoplication in terms of symptom relief. A multicenter randomized control trial is needed to assess the effect of early unselected reflux control on respiratory function and graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…8 However, our findings help explain why “not all” studies have shown that (i) distal reflux and BALF pepsin/bile acid concentrations correlate with lung function, 1 (ii) distal reflux correlates with BALF pepsin concentration, and is associated with a quicker progression to BOS 5 and (iii) fundoplication is associated with improved lung function. 30 Those patients that do respond well to fundoplication are likely those in whom GERD is an important mechanism for rejection but currently there are no comprehensive sham/placebo-controlled data (e.g., pre- and post-transplant esophageal body and LES/UES motility, using CC, impedance/pH data, BALF pepsin levels, and effect of surgery/type of surgery; oropharyngeal function etc.) available to formally explore which patients best benefit from fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, our findings help explain why “not all” studies have shown that (i) distal reflux and BALF pepsin/bile acid concentrations correlate with lung function, 1 (ii) distal reflux correlates with BALF pepsin concentration, and is associated with a quicker progression to BOS 5 and (iii) fundoplication is associated with improved lung function. 30 Those patients that do respond well to fundoplication are likely those in whom GERD is an important mechanism for rejection but currently there are no comprehensive sham/placebo-controlled data (e.g., pre- and post-transplant esophageal body and LES/UES motility, using CC, impedance/pH data, BALF pepsin levels, and effect of surgery/type of surgery; oropharyngeal function etc.) available to formally explore which patients best benefit from fundoplication.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common indication of readmission of LT recipients was intractable nausea, which was also the most common cause of readmission of NT controls. Similarly, others have reported post-LARS intractable nausea or bloating requiring readmission (up to 22%), recurrence of GERD symptoms (up to 11%), and significant weight loss in LT recipients [5,6,22,23]. However, nausea or rectal flatulence, inability to belch or vomit, and dysphagia are well-described sequelae of LARS in the nontransplant population [9,17].…”
Section: Discussionmentioning
confidence: 84%
“…Similar to our experience, Davis et al [ 21 ] also did not find any difference in estimated blood loss, duration of surgery, or length of stay between 25 LT recipients and 23 NT controls. An additional handful of small, non-comparative studies of safety outcomes of LARS in LT recipients have reported satisfactory resolution of reflux symptoms after LARS [ 5 , 22 , 23 , 25 ]. We have also demonstrated excellent control of GERD after LARS in LT recipients with objective measures such as a pH study.…”
Section: Discussionmentioning
confidence: 99%
“…ARS appears to resolve subjective symptoms of GERD in all studies that explored this as an outcome measure (16)(17)(18)(19)32). Only two study performed objective assessment of GERD in a half of their post-ARS population 14,15 , reluctance among clinicians and third-party payer organizations to subject asymptomatic individuals to invasive tests was mentioned in several articles 4,13 . Where measured, Improvements in the inflammatory infiltrate within bronchial lavage samples were also noted 19,20,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management of reflux is now recognized to be safe and effective in the lung-transplant population; many studies have demonstrated good outcomes 13,14,23,[15][16][17][18][19][20][21][22] , including in patients with end stage lung disease prior to transplantation 24 . However, the level of evidence to support ARS is low, and work needs to be done to define the optimal timing for intervention 25 , and there is an understandable reluctance to submit this group of complex patients to a randomization of therapy and timing thereof .…”
Section: Introductionmentioning
confidence: 99%